Psychological Features of Self-Regulation of Persons with Manifestations of Spiritual Crisis - Kyrylenko, Taisa; Verpeta, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
B a c k g r o u n d . The relevance of studying the problem of the role of self-regulation while person experiencing a spiritual crisis, which is the key to the harmonious development of their potential in modern conditions, is substantiated. Approaches to defining the content of the concepts of self-regulation, spirituality, and spiritual crisis are analyzed. The main components of self-regulation and their content are considered. The understanding by Ukrainian and foreign authors of spirituality, types and tendencies of the spiritual crisis is analyzed. M e t h o d s . A study was conducted based on the characteristics of the ratio of the components and the level of self-regulation with the expe¬rience of a spiritual crisis of 50 people aged 24 to 68, 25 of them are Ukrainians and 25 Poles. In order to determine the peculiarities of self¬regulation, the technique "Style of self-regulation of behavior" by V.I. Morosanova was chosen, which allows to reveal the expressiveness of the level of self-regulation and its main components: planning, modeling, programming, etc. Method of "Spiritual Crisis Diagnostics" by L.V. Shutova and A.V. Lyashchuk, which diagnosed indicators of progressive and regressive tendencies of spiritual crisis and existential vacuum was used to study the signs of spiritual crisis. R e s u l t s . According to the results of the empirical study, the dominance (64 %) of the average level of self-regulation was revealed. It was also found that the group with a low level of self-regulation, with insufficient formation of the components of modeling and programming, is charac¬terized by a greater expressiveness of experiencing a spiritual crisis with a predominance of a progressive tendency. С o n c l u s i o n . The results of the correlation analysis proved the inverse relationship of the components of self-regulation of programming and modeling with the features of experiencing a spiritual crisis, existential vacuum, in particular. Conclusions regarding age and national charac¬teristics of self-regulation of personality with manifestations of spiritual crisis are formulated.